First Mode Schumann Resonance Frequency Variation During a Solar Proton Event - Minu Sanfui; Debasish Biswas (Terrestrial, Atmospheric and Oceanic Sciences, 2016)

(untitled)
A severe X-ray flare occurred on 06 - 07 March 2012 followed by a solar proton event (SPE). During this event we studied the variation in frequency of the first Schumann resonance (SR) spectra mode from the recorded data over Kolkata (22.56°N, 88.5°E). The first mode frequency enhanced (~8.14 Hz, 3.85%) during the solar X-ray bursts and immediately after its value decreased (~7.44 Hz, 5.13%) during the proton event. The influences of SPE and X-ray bursts upon the SR frequency fluctuation are explained in terms of the changes in medium ionization, i.e., the change in dielectric property and two layer reflection height variation in the waveguide. The geomagnetic storm effect on the modification of this frequency variation occurring during that time is also considered.